PENGARUH PARTISIPASI ANGGOTA TERHADAP SISA HASIL USAHA ANGGOTA KOPERASI PERTANIAN BALAM JAYA KECAMATAN BUNUT KABUPATEN PELALAWAN - Mimi Suriani Suriani; Caskadan '; Sumarno ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine whether there is influence of the participation of the members of net income of members of the Agricultural Cooperative Balam Jaya District of Bunut Pelalawan. This research was conducted at the Agricultural Cooperative Balam Jaya District of Bunut Pelalawan. When the study was conducted from December 2014 - January 2015. The population in this study were all Members of the Cooperative Agricultural Balam Jaya District of Bunut Pelalawan amounted amounted to 57 people. In this study, researchers took samples of all of the population because the population is less than 100 by using a systematic random sampling technique (systematic random sampling technique). Data processing using SPSS 17.0. Of the t-test is known t (6.157)> t table (2,004) and Sig. (0,000) <0.05. This means that the participation of members of a significant effect on SHU.Nilai R Square of 0.408. What this means is that the contribution of variables influence the participation of members of the SHU at 59.2%. While the remaining 40.8% is influenced by other variables yan not included in this study. The simple regression equation is Y = 117,130.119 + 008 X. Keywords: Participation, SisaHasil Enterprises (SHU)